Solitons, Breathers, and Lump Solutions to the (2 + 1)-Dimensional Generalized Calogero–Bogoyavlenskii–Schiff Equation. (4th January 2021) - Ma, Hongcai; Cheng, Qiaoxin; Deng, Aiping
Abstract : In this paper, a generalized (2 + 1)-dimensional Calogero–Bogoyavlenskii–Schiff equation is considered. Based on the Hirota bilinear method, three kinds of exact solutions, soliton solution, breather solutions, and lump solutions, are obtained. Breathers can be obtained by choosing suitable parameters on the 2-soliton solution, and lump solutions are constructed via the long wave limit method. Figures are given out to reveal the dynamic characteristics on the presented solutions. Results obtained in this work may be conducive to understanding the propagation of localized waves.